A textbook of basic electrical engineering - Raychaudhuri, Barun (Chhaya prakashani, 2011)
A textbook of basic electrical engineering / Raychaudhuri, Barun. -- Kolkata: Chhaya prakashani, 2011 621.3 R263 No. of Copies : 1